2022
DOI: 10.24086/cuejhss.v6n1y2022.pp47-53
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Iraqi Political Cartoons

Abstract: Pictures have an essential effect on our thoughts and decisions.  We have also noticed how these pictures produced in the form of cartoons affect our viewpoints.  They do so since we are addicted to social media to the extent it can manipulate our thoughts unconsciously and obnoxiously. Besides, people don’t have the courage to express their viewpoints clearly, so they tend to use the satire to keep their face.  This motivates the researcher to analyze the underlying structure of this satire presented in caric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sani in Abdulwahid (2022) observed that visual metaphor is a powerful rhetoric, which can be creatively utilised to provide a better means of communicating important messages because it strongly appeals to the mind of the readers more precisely and succinctly than verbal expressions. Dweich & Al-Ghabra (2022) in their study found that the images of corruption, official irresponsibility, political failure and brutality are dominantly presented in that order.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sani in Abdulwahid (2022) observed that visual metaphor is a powerful rhetoric, which can be creatively utilised to provide a better means of communicating important messages because it strongly appeals to the mind of the readers more precisely and succinctly than verbal expressions. Dweich & Al-Ghabra (2022) in their study found that the images of corruption, official irresponsibility, political failure and brutality are dominantly presented in that order.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevance of this genre of visual commentary has been the subject of considerable scholarly exertion in recent times. On the historical development of cartooning in Africa, scholars like Abdulwahid (2022) and Jimoh in Ndago, Irikidzayi & Makombe (2022) agreed that the emergence of this genre has been influenced by a need to have an alternative platform like editorial cartoons in expressing political opinion in the face of government or regime clampdown on opposition. Hence, Dweich & Al-Ghabra (2022) in relation to the level of iconicity in their studies discussed the stylistic characteristics of the language of cartoons in some Nigerian newspapers.…”
Section: Introductionmentioning
confidence: 99%